Luminescence thermometry on the route of the mobile-based internet of things (IoT): how smart QR codes make it real - Ramalho, João F. C. B. (2019)
Quick Response (QR) codes are a gateway to the Internet of things (IoT) due to the growing use of smartphones/mobile devices and its properties like fast and easy reading, capacity to store more information than that found in conventional codes, and versatility associated to the rapid and simplified access to information. Challenges encompass the enhancement of storage capacity limits and the evolution to a smart label for mobile devices decryption applications. Organic–inorganic hybrids with europium (Eu3+) and terbium (Tb3+) ions are processed as luminescent QR codes that are able to simultaneously double the storage capacity and sense temperature in real time using a photo taken with the charge-coupled device of a smartphone. The methodology based on the intensity of the red and green pixels of the photo yields a maximum relative sensitivity and minimum temperature uncertainty of the QR code sensor (293 K) of 5.14% · K−1 and 0.194 K, respectively. As an added benefit, the intriguing performance results from energy transfer involving the thermal coupling between the Tb3+-excited level (5D4) and the low-lying triplet states of organic ligands, being the first example of an intramolecular primary thermometer. A mobile app is developed to materialize the concept of temperature reading through luminescent QR codes.